Undertaking Community Engagement for a Controlled Human Malaria Infection Study in Kenya: Approaches and Lessons Learnt - Noni Mumba; Patricia Njuguna; Patricia Njuguna; Primus Chi; Vicki Marsh; Vicki Marsh; Esther Awuor; Mainga Hamaluba; Mainga Hamaluba; Cynthia Mauncho; Salim Mwalukore; Johnson Masha; et al. (Frontiers Media S.A., 2022)
Human infection studies (HIS) involve deliberately infecting healthy volunteers with disease-causing pathogens under controlled conditions. These studies are "controlled" by way of using specific types of pathogens, including dose, and the availability of emergency medical facilities to research volunteers. Most HIS involve diseases whose treatment is known and are done to accelerate the development of novel therapeutics such as vaccines, to address emerging and existing infectious diseases. Traditionally, HIS have been conducted primarily in high-income countries (HICs) but are now increasingly being conducted in low-and-middle income countries (LMICs). In LMICs settings, HIS are likely to raise concerns among various stakeholders including participating populations and regulatory bodies, that are unfamiliar with this type of research. Deliberately infecting a healthy individual with a disease-causing pathogen seems to go against the normal practice of medicine of "do no harm". Such types of studies can give rise to increased rumors and jeopardize research participation in study activities, including non-HIS research. Community engagement can be one approach to address particular issues that HIS studies raise through meaningfully engaging with communities, where views and voices inform the conduct of HIS studies. In addition, engagement can inform the ethical conduct and acceptability of HIS studies in LMICs settings and provide opportunities for sharing information, listening to, and responding to concerns and views from potential participants, and the larger community in which the study would be conducted. Despite community engagement being an important aspect to consider, very few published and gray literature cover the types of approaches that have been used, and lessons learnt in engagement for HIS. This article outlinesthe community engagement approaches that were used to engage stakeholders and communities for malaria HIS-controlled human malaria infection (CHMI), undertaken in Kilifi, Kenya. It outlines the engagement activities across the research cycle, from activities conducted during protocol development, to planning, and implementation of the study. We discuss the challenges experienced, lessons learnt, and provide some recommendations for engagement around HIS.